A dominant sulfhydryl-containing protein in the outer membrane of Neisseria gonorrhoeae. - Norrod, E P (1993)
By using a method that labels sulfhydryl-containing proteins in situ, we have detected a major outer membrane protein of Neisseria gonorrhoeae at 41 kDa. A protein of this molecular mass has not previously been shown to be a major outer membrane protein in gonococci. In addition, a minor protein rich in cysteinyl residues was detected at 31.5 kDa.